Is 'Group and Save' Blood Request Routinely Required for Nasopharyngeal Biopsy? - Foster Tochukwu Orji; Nekwu E Okolugbo (Archives of Otolaryngology and Rhinology - Peertechz Publications, 2017)
Objectives: To establish our current practice of 'group and save' blood for nasopharyngeal tumour biopsy (NB), and to determine the rate of blood transfusions among patients who underwent NB under general anaesthesia.  Methods: A retrospective chart review of all patients who underwent biopsy of NB in our tertiary institution between January 2006 and December 2015 was undertaken. Those with Juvenile nasopharyngeal angiofi broma were excluded. Data retrieved included patients' characteristics such as age/sex, anaemia, primary tumour extension, and histology. Outcome measures included rate of 'group and save blood' requests, intra-operative blood loss, blood transfusion rates. Comparison was made between those that were requested to group and save blood prior to surgery (group 'A') and the group 'B' that were not so requested.  Results: We analysed eligible 103 cases (71 males and 32 females) out of 121 nasopharyngeal biopsies over the study period. 'Group and save' blood was undertaken in 47.6% (49/103) of our patients. Only 12.2% of the requested blood was transfused. Among evaluated patient characteristics, only oropharyngeal tumour extension differ between the study groups (P = 0.025). Overall, 14% had signifi cant intra-operative blood loss (>500mls), while 9.7% were transfused. The rates of blood loss and transfusion were not signifi cantly different between the study groups (P = 0.22 and 0.09 respectively). Signifi cant factors that infl uenced transfusion were pre-operative anaemia and oropharyngeal tumour extension.  Conclusion: There was high rate of arbitrary request for 'group and save blood' prior to NB in our institution over the last decade, which seems largely unnecessary. We recommend it be undertaken only in the presence anaemia and extensive oropharyngeal tumour extension.